(untitled) (Al-Qamar, 2018)
In this article life of a prominent Muslim scholar named Abdul Haq has been discussed by different aspects of his life was a Pakistani Islamic scholar and the founder, chancellor, and Shaykh al-Hadith of the Islamic seminary Darul Uloom Haqqania. He was involved in politics as a member of the political party Jamiat Ulema-e-Islam. He served three times in the National Assembly of Pakistan and was an active proponent of the Khatm-i Nabuwwat movement. Abdul Haq completed his religious education in India at Darul Uloom Deoband. He taught at Deoband for four years until difficulties arose due to the independence of Pakistan. In 1947, he founded Darul Uloom Haqqania in Akora Khattak, one of the first Islamic seminaries to be established in Pakistan. He taught hadith at the madrasah for the rest of his life and was well known by the title "Shaykh al-Hadith". His son, Sami ul Haq, succeeded him as chancellor of Darul Uloom Haqqania. Abdul Haq’s sermons have been published by his son in two volumes containing over 1,300 pages, entitled Da`wat-i Haq